EP250/#199 Intraoperative predictors of appendiceal abnormalities in mucinous ovarian neoplasms. (4th December 2022) - Lavecchia, Melissa; Dubey, Anisha; Eiriksson, Lua
Abstract : Objectives: The aim of this study was to evaluate intraoperative factors associated with pathological abnormalities of the appendix at time of gynecologic oncology surgery for mucinous ovarian neoplasms (MONs). Methods: We conducted a retrospective cohort study of 225 patients with pathology confirmed MON (cystadenoma, borderline tumor, and adenocarcinoma). Eligible patients underwent surgery for an adnexal mass with concurrent appendectomy between 2000–2018. Pathological findings of the appendix were categorized and intraoperative factors, such as tumor frozen section and surgeon's impression of the appendix were analyzed using descriptive statistics and logistic regression. Results: Most patients' appendixes were unremarkable on final pathology (77.8%). One patient with adenocarcinoma had metastatic spread to the appendix. Twenty-three patients (10.2%) had low-grade appendiceal mucinous neoplasms, where 22/23 were in the setting of malignancy, and one patient had a mucinous borderline ovarian tumor. Both abnormal intraoperative surgical impression of the appendix and malignant frozen section were independent predictors of abnormal appendix on final pathology, OR 11.19 (95%CI 4.38–28.60) and OR 3.23 (95%CI 1.35–7.76), respectively. When combining normal intraoperative appearance of the appendix and benign ovarian tumor on frozen section, specificity was found to be 86%, with seven (14%) patients being misclassified. Conclusions: Frozen section of the ovary suggesting malignancy and abnormal surgical appearance of the appendix were highly associated with abnormal appendix on final pathology. However, benign frozen section and normal appearing appendix are poor predictors of pathological findings of the appendix. Appendectomy should be considered in all cases of MONs, regardless of intraoperative findings.